Optimalisasi Kinerja Karyawan Melalui Pelatihan, Pengembangan Karir dan Lingkungan Kerja di Industri F&B Jakarta Selatan - Anwarisa, Budi; Soekotjo, Sundari (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research aims to analyze training, career development and work environment on employee performance. This research used a survey method with a sample of 64 people using the Saturated Sampling Formula technique. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique uses the SPSS Version 27 application. Which includes validity tests, reliability tests, correlation tests, multiple linear regression tests and classical assumption tests. The research results provide the conclusion that training, career development and work environment simultaneously influence employee performance. The determinant coefficient (R^2) of employee performance is 0.428, indicating that the influence of training, career development and work environment on employee performance is 42.8%, while the remaining 57.2.3% is influenced by other variables outside the research conducted. Therefore, this research suggests the need to improve training, career development and work environment in order to improve employee performance